Detection of Antibiotic Residues and Isolation of Antibiotic Resistant Escherichia Coli from Chicken Meat and Chickens in Malaysia - Tin, Tin Myaing (2003)
Public health is intrinsically related to food animal production. Antibiotic residues in the food of animal origin and antibiotic resistant bacteria threaten human health. There is an increase in population and the demand for chicken meat in Malaysia is also increasing. Not much data is available on antibiotic residues and antibiotic resistant E. coli from chickens and foods of animal origin in Malaysia. In this study, a total of 400 chicken meat samples were subjected to antibiotic residues screening tests. The prevalence of antibiotics residues in chicken meat was between 111% to 217%, using three microbial growth inhibition tests; namely, fast antimicrobial screening test (FAST), Baedlus stearothermophdus disc assay (BSDA) and a commercial test kit (TAT) with reference to four plate test (FPT) The test performances were evaluated on sensitivity, specificity, positive predtcnve value and negative predictive value. The sensitivity of these tests ranged from 55.6 to 65% and specificity, from 82 to 90.6%. Kappa agreement was between 0.5 to 0.8. Based on the above performance parameters, as well as the cost, simplicity and incubation period, BSDA is a screening test of choice. A total of 182 E. coli isolates from these chicken meat samples were found resistant to twelve antibiotics; vancomycin (99.4%), trimethoprim (98.9%), nalidixic acid (97.2%), tetracycline and cephradine (96.7%), ampicillin (94.5%), enrofloxacin (83.5%), erythromycin (82.9%), ciprofloxacin (81.3%), cefoperazone (80.2%), chloramphenicol (74.4%) and kanamycin (68.6%). Forty-six antibiotypes and nine antibiogroups were observed. Escherichia coli isolated from antibiotic residues positive samples and antibiotic residues negative samples were tested for antibiotic susceptibility to twelve antibiotics. A higher percentage of antibiotic resistance was observed in E. coli isolates from antibiotic residues positive samples compared to those from antibiotic residues negative samples. 58.3% and 29.2% of E. coli isolates from antibiotic residues positive samples and 25% and 17.1% of E. coli isolates from antibiotic residues negative samples were resistant to 12 and 11 antibiotics, respectively. Plasmid isolation was conducted in 132 of the E. coli isolated. Plasmid occurrence rate of 81.8% were observed in this study with high diversity of plasmids profiles among E. cob isolates from different sources. The number of plasmids ranged from 0 to 8 and the sizes of plasmids ranged from 1.2 MDa to 118.6 MDa. Forty-five different plasmid profiles were observed. No apparent correlation was found between the plasmid profiles of the strains and their antibiotic resistance patterns. In another study, the occurrence of antibiotic resistant E. coil was determined in four flocks where in three flocks, chickens were given commercial feed containing antibiotics and in one flock the feed given were without antibiotics. Escherichia colt isolates from chickens given feed without antibiotics showed low resistance to all antibiotics even at one day old. The screening of antibiotic residues was done in 20 of these chickens at the age of 42 days old. The occurrence of antibiotic residues was 10% in chickens given feed containing antibiotics. It was observed that E. coli isolates from the antibiotic residues positive samples were also resistant to 12 antibiotics while those from antibiotic residues negative samples were resistant to 2-8 antibiotics. This observation requires further investigation. Klebseilla spp., Pseudomonas spp. and E. coil were isolated from the feeds and water of the flock where chickens given feed without antibiotics. All these bacteria were resistant to 4-10 antibiotics. Antibiotic resistant E. coli was observed in day-old chicks without any selective pressure, such as even when no antibiotic was added to the ration. Thus, proliferation of antibiotic resistant E. colt is less dependent on the use of antibiotics/antimicrobials in poultry farms and most likely that chickens obtain antibiotic resistant E. colt from the environment.